2019
DOI: 10.1130/g46578.1
|View full text |Cite
|
Sign up to set email alerts
|

Modeling petroleum expulsion in sedimentary basins: The importance of igneous intrusion timing and basement composition

Abstract: The concept of a critical moment in a petroleum system (the time of highest probability of entrapment and preservation of oil and gas) has underlain petroleum exploration for over 25 years. However, one area where understanding the critical moment is challenging is the Faroe-Shetland Basin (FSB; offshore UK). Isotopic dating of oils suggests that petroleum generation began between ca. 68 and 90 Ma; however, most basin models invoke an earlier generation beginning in the mid-Cretaceous at ca. 100 Ma, predating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 25 publications
(42 reference statements)
0
4
0
Order By: Relevance
“…Gac et al, 2014), this effect has hitherto not been taken into account (cf. Gardiner et al, 2019) in the GBSB. Accounting for the intrusions leads to an ca.…”
Section: F I G U R E 1mentioning
confidence: 99%
“…Gac et al, 2014), this effect has hitherto not been taken into account (cf. Gardiner et al, 2019) in the GBSB. Accounting for the intrusions leads to an ca.…”
Section: F I G U R E 1mentioning
confidence: 99%
“…Malthe-Sørrenssen et al, 2004;Hansen and Cartwright 2006); West of Shetland (e.g. Rateau et al, 2013;Gardiner et al, 2019); and the southern and north-western margins of Australia (e.g. Holford et al, 2012;Mark et al, 2020).…”
Section: Wider Implicationsmentioning
confidence: 99%
“…Brooks Hanson, 1995;Rodriguez-Monreal et al, 2009;Senger et al, 2014;Aarnes et al, 2015;Gardiner et al, 2019), as too has been the hydrothermal fluid flow associated with their emplacement (e.g. Rossetti et al, 2007;Scott et al, 2015).…”
mentioning
confidence: 99%
“…Aydin, 1978;Underhill and Woodcock, 1987;Shipton and Cowie, 2001;Wibberley et al, 2007). Numerous studies have shown that deformation bands can have a significant influence on fluid flow Aydin, 1994, 1995;Gibson, 1998;Sigda et al, 1999;Fossen and Bale, 2007;Ballas et al, 2015). Due to their mode of formation (i.e.…”
Section: Introductionmentioning
confidence: 99%